2018
DOI: 10.18357/ijcyfs94201818643
|View full text |Cite
|
Sign up to set email alerts
|

“Special” Families and Their “Normal” Daily Lives: Family Quality of Life and the Social Environment

Abstract: This article focuses on the social and societal factors that influence family quality of life (FQOL). In this qualitative study from the Netherlands, a multiple case study design was used, in which members of families having a child or children with intellectual and developmental disabilities talked about their experiences during interviews. The data were analysed through a rigorous inductive thematic analysis. Our findings relate to the families’ experiences with their social environment and especially with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…This is reflected by other studies on family quality of life where families that include a member with disabilities reported positive aspects on their family life, such as problem solving and family sense of coherence [37]. Results from worldwide research on family quality of life show that positive family relationships are a common strength of most families where one or more members have a disability [69], where negative feelings are likely to be attributed to societal norms that are imposed on families [70].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 88%
“…This is reflected by other studies on family quality of life where families that include a member with disabilities reported positive aspects on their family life, such as problem solving and family sense of coherence [37]. Results from worldwide research on family quality of life show that positive family relationships are a common strength of most families where one or more members have a disability [69], where negative feelings are likely to be attributed to societal norms that are imposed on families [70].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 88%
“…In a recent study on families with a family member with disabilities (Boelsma et al . ), it was found that families felt confronted by what is considered to be normal in their daily lives through their interactions with others. To reduce this form of sigma, referred to as associative or family stigma, interventions need to include families where disability is the case (Mitter et al .…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In Western society, political developments are trending towards informal networks providing more care, resulting in families that increasingly fulfil a central role in the support and care of their children with disabilities, including into adulthood (Boelsma et al . ; Brown et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…Because normalcy is a widely accepted concept, it is not surprising that studies have found that parents perceive themselves as not being able to live a normal life due to disability in their families (Neely-Barnes & Dia, 2008). In a recent in-depth study of family quality of life (Boelsma, Schippers, Dane, & Abma, 2018), this view was corroborated and explained. Families felt confronted by normspresumed standards related to what is considered normal-in their daily lives through their interactions with others.…”
Section: Family Quality Of Life and The New Eugenicsmentioning
confidence: 97%